The synergy between museums, culture, and well-being: a new way to health - Ciliberti, Rosagemma; Fusco, Roberta (Medicina Historica, 2023)
As repositories of culture and history, museums play a key role in promoting well-being and fostering a healthier society. Through various mechanisms, such as education, social engagement and therapeutic interventions, museums contribute significantly to improving mental health, social cohesion and overall quality of life. For these reasons, it is necessary to promote the potential of museums so that culture and health become actors in an increasingly virtuous project and activity relationship.